Radiologist participation in multi‐disciplinary teams in breast cancer improves reflective practice, decision making and isolation. (27th December 2013) - Alcantara, S.B.; Reed, W.; Willis, K.; Lee, W.; Brennan, P.; Lewis, S.
<x xml:space="preserve">Abstract</x> This study aims to explore Australian radiologists' experiences of participating in breast cancer multi‐disciplinary team (MDT) meetings to identify enablers and barriers to participation as well their perception of confidence and patient care. Qualitative methods incorporating observation and interviews were used. Twenty‐one breast cancer MDT meetings were observed across Sydney to study the dynamics of the meetings, the level of participation by radiologists and their most important interactions. Qualitative semi‐structured interviews were conducted with 10 radiologists participating in these meetings regarding participation, educational opportunities and improvements to work practices. Radiologists' participation in breast cancer MDT meetings is influenced by the type of meeting they attend with higher levels of participation and a more dominant 'valued' role being evident in pre‐interventional meetings. The key themes to emerge from the data include the importance of 'sharing experiences', the 'radiologist–pathologist relationship' and the value of 'continuing participation'. Radiologists believed their confidence in their clinical decision making increased when there was immediate feedback from pathologists. This study highlights the benefits of radiologists regularly participating in breast cancer MDT meetings in terms of continuing professional education resulting from collegial experiential learning. Radiologists' perceived patient care and workplace isolation were improved by sharing experiences with other cancer care colleagues.